Como os adultos aprendem a ler?: evidências de um estudo com adultos pouco alfabetizados e crianças com a mesma habilidade de leitura - Marcela Fulanete Correa (2009)
The present study investigated whether the same cognitive processes are involved in beginning literacy acquisition by children and adults. Sixty-one Brazilian adults, enrolled in a literacy program in a major Brazilian city, participated in the study. They ranged in age from 16 to 80years. Sixty-one typically developing 1st, 2nd and 3rd graders also participated in the study. They varied in age from 6 to 9 years, and were individually matched with the 61 adults on the basis of word reading ability. All participants were administered tasks that evaluated reading,spelling and arithmetic abilities, letter-name knowledge, phonological awareness, rapid serial naming, verbal short-term memory, verbal intelligence, and orthographic coding skills. Results suggested that, relative to children of the same reading level, adults learning to read in Portuguese present difficulties in sound segmentation. Indeed, an analysis of the participants responses on an experimental spelling task revealed that, unlike the childrens errors, most of the errors made by the adults consisted of what Ehri (1992) has dubbed partial alphabeticspellings. However, in spite of these difficulties, our results strongly suggest that adults in literacy programs are sensitive to letter-sound regularities in words and, similar to children, rely on phonological coding skills to learn to read and spell. In fact, regression analyses showed thatvariations in phonological awareness and rapid serial naming contributed significantly to variations in the reading and spelling ability of the children and adults who participated in the present study. As far as the correlates of word reading and spelling ability are concerned, onlyone difference was found between the adults and the children. Specifically, variations in verbal intelligence were not correlated with variations in reading and spelling ability among the adults. On the other hand, variations in verbal intelligence accounted for a unique portion of the variance in reading and spelling skills among the children, even after we controlled for the effect of individual differences in theoretically important abilities. Finally, the adults who participated in the present study found it particularly difficult to spell words containing soundswhose spelling depends on the syntactic category of the word, suggesting that, in addition to phonological difficulties, adults with low literacy skills have difficulty with the morphosyntactic component of language.